Transitivity Analysis in Detecting Fraudulent Language in Email: Forensic Linguistics Approach - Rifki, Yudia; Sawirman, Sawirman; Usman, Fajri (IJOLTL (Indonesian Journal of Language Teaching and Linguistics), 2021)
This research discusses the analysis of transitivity in detecting the fraudulent language in email fraud. The research purposes are (1) to identify the process types of transitivity systems in clauses used in email fraud, and (2) to explain how the fraudulent language is identified by using the transitivity system. This research is conducted descriptively. The documentation recording method is applied in collecting the data. Halliday’s theory of Systemic Functional Linguistics, particularly the transitivity system is used to analyze the data. The research result is presented in the form of a table of process types and data interpretation. The data analysis resulted that the sender dominantly used the material process to construe the fraudulent language by realizing the misleading statements. It is used to deceive and convince the email recipients by creating the false representation of important and powerful figures that influence the reader to believe the messages.